A Quininib Analogue and Cysteinyl Leukotriene Receptor Antagonist Inhibits Vascular Endothelial Growth Factor (VEGF)-independent Angiogenesis and Exerts an Additive Antiangiogenic Response with Bevacizumab - Butler, Clare T. (J Biol Chem, 2017)
Excess blood vessel growth contributes to the pathology of metastatic cancers and age-related retinopathies. Despite development of improved treatments, these conditions are associated with high economic costs and drug resistance. Bevacizumab (Avastin®), a monoclonal antibody against vascular endothelial growth factor (VEGF), is used clinically to treat certain types of metastatic cancers. Unfortunately, many patients do not respond or inevitably become resistant to bevacizumab, highlighting the need for more effective antiangiogenic drugs with novel mechanisms of action. Previous studies discovered quininib, an antiangiogenic small molecule antagonist of cysteinyl leukotriene receptors 1 and 2 (CysLT(1) and CysLT(2)). Here, we screened a series of quininib analogues and identified a more potent antiangiogenic novel chemical entity (IUPAC name (E)-2-(2-quinolin-2-yl-vinyl)-benzene-1,4-diol HCl) hereafter designated Q8. Q8 inhibits developmental angiogenesis in Tg(fli1:EGFP) zebrafish and inhibits human microvascular endothelial cell (HMEC-1) proliferation, tubule formation, and migration. Q8 elicits antiangiogenic effects in a VEGF-independent in vitro model of angiogenesis and exerts an additive antiangiogenic response with the anti-VEGF biologic bevacizumab. Cell-based receptor binding assays confirm that Q8 is a CysLT(1) antagonist and is sufficient to reduce cellular levels of NF-κB and calpain-2 and secreted levels of the proangiogenic proteins intercellular adhesion molecule-1, vascular cell adhesion protein-1, and VEGF. Distinct reductions of VEGF by bevacizumab explain the additive antiangiogenic effects observed in combination with Q8. In summary, Q8 is a more effective antiangiogenic drug compared with quininib. The VEGF-independent activity coupled with the additive antiangiogenic response observed in combination with bevacizumab demonstrates that Q8 offers an alternative therapeutic strategy to combat resistance associated with conventional anti-VEGF therapies.